Capital Conversion Analysis in the Transition from Conventional to Islamic Banking: A Case Study in West Nusa Tenggara - Nurul Wathoni Fauzan; Andi Putradi (Shar-E: Jurnal Kajian Ekonomi Hukum Syariah)
This study examines the capital conversion process in the transformation of Bank NTB from a conventional bank to an Islamic bank, focusing on the regulatory, institutional, and operational aspects involved. Using a qualitative literature review method, this study explores the institutional restructuring and financial implications of the conversion process. The results of the study indicate that despite a temporary decline in financial performance indicators during the transition period, Bank NTB Syariah managed to record an increase in asset growth, third-party funds (DPK), and financing in the following years. This study concludes that the success of the conversion is highly dependent on strategic planning, organizational synchronization, and the effective implementation of Islamic economic principles. This study contributes to the literature on institutional transformation in the Islamic banking sector in Indonesia.